Case report: Concurrent intrathecal and intravenous pembrolizumab for metastatic melanoma with leptomeningeal disease - Dan, Xiang; Huang, Mengxi; Sun, Zhaochen; Chu, Xiaoyuan; Shi, Xin; Chen, Yitian (Frontiers in Oncology, 2024)
Leptomeningeal disease (LMD) is a serious cancer complication associated with a poor prognosis.Approximately 5-25% of patients with melanoma develop LMD. Currently, no standard treatment protocol exists, and very few cases have been reported. Despite ongoing advances in new therapies, LMD treatment options remain limited. Here, we report a case of intrathecal pembrolizumab administration in a patient with melanoma and LMD. Intrathecal pembrolizumab administration was feasible and safe at the tested dose. Drawing from this case, along with our expertise and the existing evidence on systemic immunotherapy, we propose that the immunotherapy approach involving intrathecal administration for patients with LMD from melanoma warrants additional exploration in clinical trials.